Além do Arco Iris - Hovdenakk, Per (São Paulo : FAAP - fundação Armando Alvares Penteado, 1998)
Cunha, Alexandre da ; Malta, Antônio ; Almeida, Efraiin ; Verzuti, Erika ; Leirner, Jac ; Loeb, Lucia Mindlin ; Cipis, Marcelo ; Marepe ; Lacerda, martha ; Restife, mauro ; Kaepler, Sabine ; Pessoa, Solange ; Lemos, Tonico ; Ono, Yoko
biografie
Além do Arco Iris / Beyond the rainbow, FAAP - fundação Armando Alvares Penteado, São Paulo, 15.09 - 04.10.1998
Engels & Portugees
boek